RANCANG BANGUN MODUL PRAKTIKUM SISTEM EMBEDDED BERBASIS RASPBERRY PI (PENGONTROLAN DASAR LED, LED DOT-MATRIX, DAN SEVEN SEGMENT DISPLAY) - Abdul Hadi, Muhammad; Rahardjo, Pratolo; Elba Duta Nugraha, I Putu (Jurnal SPEKTRUM; Vol 8 No 2 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i02.p33, 2021)
Embedded system is microprocessor-based systems that are used to perform certain functions. Embedded systems learning is very much needed, especially for students of Electrical Engineering, Faculty of Engineering, Udayana University. This is evidenced by the existence of a new course, namely the Embedded + Lab System. To support the convenience of practicum in the laboratory, in this study, an Embedded+Lab System practical guide will be designed and built by utilizing the Single Board Microcomputer Raspberry Pi. It is hoped that this Embedded+Lab System practical guide will be useful for Electrical Engineering students, Faculty of Engineering, Udayana University. This research carried out several basic designs that will be used in the Embedded System module 1 practical experiment, namely the design of a Light Emitting Diode (LED) control, LED DOT-Matrix, and seven segment display. The design of each control system will generally be divided into two parts, namely hardware design and software design. The results of this study are a box 1 system embedded practical module and practical guides, as well as the design of each control system, all of which work well.